Composite membrane material for reducing content of Au / Ag / Pt / Ni / Bi in electronic grade sulfuric acid and preparation method

By using a composite membrane material of PVDF/SGO nanoporous membrane material and PVDF/GO electrospinned membrane material, the problem of high content of specific metal ion impurities in electronic-grade sulfuric acid is solved, efficient metal ion removal and sulfuric acid purification are achieved, and product quality and membrane life are improved.

CN119838580AActive Publication Date: 2025-04-18FOSHAN XILONG CHEM CO LTD
View PDF 14 Cites 0 Cited by

Patent Information

Application Number
CN202411970159.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-30
Publication Date
2025-04-18
Estimated Expiration
2044-12-30

AI Technical Summary

Technical Problem

In the existing electronic-grade sulfuric acid purification methods, the content of specific metal ions is high, which affects the performance and product quality of sulfuric acid.

Method used

A composite film material of PVDF/SGO nanoporous membrane material and PVDF/GO electrospinning membrane material is prepared by scraping film and electrospinning technology to increase the adsorption and removal of Au, Ag, Pt, Ni, and Bi metal ions in electronic-grade sulfuric acid.

Benefits of technology

It effectively reduces the content of specific metal ions in electronic-grade sulfuric acid, improves the purity and performance of sulfuric acid, meets high purity requirements, and extends the service life of the film material.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119838580A_ABST
    Figure CN119838580A_ABST
Patent Text Reader

Abstract

The invention discloses a composite membrane material for reducing the content of Au / Ag / Pt / Ni / Bi in electronic-grade sulfuric acid and a preparation method. The composite membrane material comprises a PVDF / SGO nano-porous membrane material and a PVDF / GO electrostatic spinning membrane material compounded on the surface of the nano-porous membrane material, according to the nano-porous membrane material, N-methyl pyrrolidone is used as a solvent, polyvinylidene fluoride is used as a polymer, glass fibers and graphite powder are used as additives, SGO is used as a complexing agent, the materials are prepared into membrane liquid, and the PVDF / SGO nano-porous membrane material is obtained through membrane scraping and coating. According to the electrostatic spinning membrane material, N, N-dimethylformamide serves as a solvent, polyvinylidene fluoride serves as a polymer, graphene oxide serves as a complexing agent, the solvent, the polymer and the graphene oxide are prepared into membrane forming liquid, and the PVDF / GO electrostatic spinning membrane material is obtained through spinning. The composite membrane material can effectively solve the problem of high content of specific metal ion impurities such as Au, Ag, Pt, Ni and Bi in existing high-purity sulfuric acid purification.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of electronic chemical products, and in particular to a composite film material for reducing the content of Au / Ag / Pt / Ni / Bi in electronic grade sulfuric acid and a preparation method thereof. Background Art

[0002] Electronic grade sulfuric acid is also known as ultrapure sulfuric acid, high purity sulfuric acid, etc. As a chemical reagent, it is widely used in integrated circuits (IC), semiconductors and other microelectronics industries. In the wafer production process, electronic grade sulfuric acid is mainly responsible for photolithography, cleaning, corrosion, etc. of the wafer, which can effectively remove inorganic residues, impurity particles and carbon deposits on the wafer, thereby ensuring the quality and performance of the wafer. In addition, electronic grade sulfuric acid can also be used as a solution, mostly used in the production of electrolytes for lithium batteries and other rechargeable batteries.

[0003] There are two main methods for preparing electronic grade sulfuric acid: the industrial sulfuric acid distillation method, which uses industrial sulfuric acid as raw material and adds a strong oxidant for distillation, and can produce finished products on a small scale; the sulfur trioxide gas absorption method, which uses ultrapure water to directly absorb clean sulfur trioxide gas to produce finished products, and can be produced on a large scale. Among them, the distillation method has high energy consumption and high cost, and some impurities are difficult to remove. The waste gas and acid mist generated are harmful to the human body and are not conducive to environmental protection. It is only suitable for small-scale production. The sulfur trioxide gas absorption method is to purify sulfur trioxide gas, and then absorb it with ultrapure water or washed sulfuric acid to produce high-purity sulfuric acid. This method can effectively avoid the above-mentioned shortcomings of the distillation method, but the existing gas absorption method cannot effectively remove sulfur dioxide gas, so that the prepared sulfuric acid contains a certain amount of trace sulfur dioxide impurities, which affects the performance of sulfuric acid.

[0004] With the rapid development of my country's integrated circuit, semiconductor and lithium battery markets, the continuous advancement of technology and the continuous improvement of component precision, electronic-grade sulfuric acid plays a vital role in the manufacturing process of integrated circuits, semiconductors and lithium batteries. Especially in the cleaning and etching process of silicon wafers, the presence of heavy metal impurities has a significant impact on the performance of electronic-grade sulfuric acid:

[0005] 1. Affecting the quality and production yield of wafers: In the semiconductor manufacturing process, sulfuric acid is mainly used to clean and etch wafers. The presence of Ag impurity ions will form tiny particles or defects on the surface of the wafer, which will affect the quality and production yield of the wafer, resulting in more scrap and rework.

[0006] 2. Impact on the diffusion effect of the diffusant: Impurity ions such as Au will affect the diffusion effect of the diffusant.

[0007] 3. Reduce etching effect: Metal Pt has strong chemical stability and low solubility. Therefore, when it exists as an impurity in electronic-grade sulfuric acid, Pt impurity ions may reduce the corrosiveness of sulfuric acid and reduce its etching effect. In addition, the presence of Pt impurity ions in electronic-grade sulfuric acid may affect the activity and solubility of electronic-grade sulfuric acid on metal surfaces.

[0008] 4. The insulation voltage resistance decreases: Alkali metal impurities such as Ni, Na, and Ca will melt into the oxide film, resulting in a decrease in the insulation voltage resistance.

[0009] 5. Impact on integrated circuit performance: Heavy metal impurities such as Bi and Cr, when attached to the surface of silicon wafers, will reduce the withstand voltage of the P-N junction and affect the electrical performance of the integrated circuit (IC).

[0010] 6. Reduce IC yield: During the processing of silicon wafers, insoluble solid particles or metal ions may conduct electricity between fine circuits and cause short circuits. A few metal ions or dust are enough to make ICs with smaller line widths scrapped, resulting in a drop in IC yield of about 50%.

[0011] 7. Photolithography defects and uneven oxide layer: Dust particles can cause photolithography defects and uneven oxide layer, affecting the plate making quality and plasma etching process.

[0012] Therefore, in order to obtain high-quality and high-yield integrated circuit chips, very pure electronic-grade sulfuric acid must be used to clean silicon wafers to remove various contaminants and reduce the impact of heavy metal impurities. This requires the development of an electronic-grade sulfuric acid with extremely low heavy metal content to solve the problem of high content of specific metal ion impurities in the existing electronic-grade sulfuric acid purification, so as to meet the high purity requirements of various industries for electronic-grade sulfuric acid and the sharp increase in the demand for high-purity sulfuric acid. Summary of the invention

[0013] In order to overcome the deficiencies of the prior art, one of the objectives of the present invention is to provide a composite film material for reducing the content of Au / Ag / Pt / Ni / Bi in electronic grade sulfuric acid.

[0014] A second object of the present invention is to provide a method for preparing a composite film material for reducing the content of Au / Ag / Pt / Ni / Bi in electronic grade sulfuric acid.

[0015] One of the purposes of the present invention is achieved by the following technical solution: a composite membrane material for reducing the content of Au / Ag / Pt / Ni / Bi in electronic grade sulfuric acid, the composite membrane material comprising a PVDF / SGO nanoporous membrane material, and a PVDF / GO electrostatic spinning membrane material composited on the surface of the PVDF / SGO nanoporous membrane material;

[0016] The PVDF / SGO nanoporous membrane material uses N-methylpyrrolidone as a solvent, polyvinylidene fluoride as a polymer, glass fiber and graphite powder as additives, and sulfonated graphene oxide as a chemical adsorption complexing agent, and is configured into a membrane liquid with a viscosity suitable for scraping and stable, and is coated by scraping to obtain a PVDF / SGO nanoporous membrane material;

[0017] The PVDF / GO electrostatic spinning membrane material uses N,N-dimethylformamide as a solvent, polyvinylidene fluoride as a polymer, and graphene oxide as a chemical adsorption complexing agent, which are configured into a stable membrane solution with a viscosity suitable for electrostatic spinning, and the PVDF / GO electrostatic spinning membrane material is obtained through spinning.

[0018] Optionally, in the PVDF / SGO nanoporous membrane material, the mass ratio of N-methylpyrrolidone to polyvinylidene fluoride is 85-95:5-15, and the sum of the mass percentages of the two components is 100%; the amount of the glass fiber is 5-20% of the total mass of N-methylpyrrolidone and polyvinylidene fluoride, the amount of the graphite powder is 5-15% of the total mass of N-methylpyrrolidone and polyvinylidene fluoride, and the amount of the graphene oxide is 0.5-2% of the total mass of N-methylpyrrolidone and polyvinylidene fluoride.

[0019] Optionally, in the PVDF / GO electrospinning membrane, the mass ratio of N,N-dimethylformamide to polyvinylidene fluoride is 85-95:5-15, the sum of the mass percentages of the two components is 100%, and the amount of graphene oxide used is 0.01-6% of the total mass of N,N-dimethylformamide and polyvinylidene fluoride.

[0020] Optionally, the molecular weight of the polyvinylidene fluoride is 300,000 to 500,000.

[0021] Optionally, the composite membrane material is at least a three-layer structure, including a PVDF / SGO nanoporous membrane material and a PVDF / GO electrostatic spinning membrane material respectively composited on the upper surface and the lower surface of the PVDF / SGO nanoporous membrane material.

[0022] The second object of the present invention is achieved by adopting the following technical solution: a method for preparing a composite film material for reducing the content of Au / Ag / Pt / Ni / Bi in electronic grade sulfuric acid, comprising the following steps:

[0023] (1) Weighing 85-95% by weight of N-methylpyrrolidone and 5-15% by weight of polyvinylidene fluoride, the sum of the mass percentages of the two components being 100%, and mixing the above components to prepare a basic scraping film solution; weighing 0.01-6% by weight of graphene oxide based on the total weight of the basic film solution, and then mixing it with the basic film solution to prepare an electrospinning film solution for standby use;

[0024] (2) Weighing 85-95% by weight of N,N-dimethylformamide and 5-15% by weight of polyvinylidene fluoride, the sum of the mass percentages of the two components being 100%, and mixing the above components to prepare a basic scraping liquid; weighing 5-20% by weight of glass fiber, 5-15% by weight of graphite powder, and 0.5-2% by weight of sulfonated graphene oxide based on the total weight of the basic scraping liquid, and mixing them with the basic scraping liquid to prepare a scraping liquid;

[0025] (3) pouring the scraping liquid obtained in step (2) into a scraping coater, scraping the film on a quartz plate using the scraping coater, and then soaking the film in ultrapure water for 1 to 24 hours, and drying it for 1 to 3 hours after demolding to obtain a PVDF / SGO nanoporous membrane material;

[0026] (4) Using an electrospinning machine, the electrospinning membrane solution prepared in step (1) is spun on the upper and lower surfaces of the PVDF / SGO nanoporous membrane material in step (3) to form upper and lower layers of PVDF / GO electrospinning membrane material, and after drying for 0.5 to 2 hours, a composite membrane material is obtained.

[0027] Optionally, the specific method for preparing the electrospinning membrane solution in step (1) is as follows:

[0028] (11) preparing a base membrane solution: weighing N,N-dimethylformamide and polyvinylidene fluoride, mixing the above components, stirring for 1 to 3 hours in a stirrer, and vacuum defoaming for 5 to 30 minutes to obtain a base membrane solution;

[0029] (12) Preparing an electrospinning membrane solution: Weighing graphene oxide, mixing the graphene oxide with the base membrane solution obtained in step (11), stirring with a stirrer for 1 to 3 hours, and vacuum defoaming for 5 to 30 minutes to obtain an electrospinning membrane solution.

[0030] Optionally, the specific preparation method of the scraping liquid in step (2) is as follows:

[0031] (21) preparing a basic scraping solution: weighing N-methylpyrrolidone and polyvinylidene fluoride, mixing the above components, stirring for 1 to 3 hours in a stirrer, and vacuum defoaming for 5 to 30 minutes to obtain a basic scraping solution;

[0032] (22) preparing a scraping liquid: weighing glass fiber, graphite powder, and sulfonated graphene oxide, mixing the glass fiber, graphite powder, sulfonated graphene oxide, and the basic scraping liquid obtained in step (21), stirring in a mixer for 1 to 3 hours, and vacuum defoaming for 5 to 30 minutes to obtain a scraping liquid.

[0033] Optionally, in step (3), the process parameters of the scraping coater are as follows: the reciprocating scraping speed is 8 to 12 mm / s, the scraping temperature is at room temperature, and the film thickness of the film scraped by the scraping coater on the quartz plate is 200 to 1000 μm.

[0034] Optionally, in step (4), the spinning conditions are: spinning voltage is 8 to 16 kV, injection speed is 0.6 to 1.4 mL / h, and spinning time is 2 to 8 h.

[0035] Compared with the prior art, the present invention has the following beneficial effects:

[0036] (1) The present application prepares a new type of super adsorption material - a composite membrane material containing PVDF / SGO nanoporous membrane material and PVDF / GO electrospinning membrane material, which can effectively solve the problem of high content of specific metal ion impurities in the existing high-purity sulfuric acid purification, especially the high removal ability of Au, Ag, Pt, Ni, and Bi metal ions.

[0037] In specific application scenarios, the composite membrane material of the present invention is arranged in an existing distillation device for purifying sulfuric acid, specifically, it is arranged behind a four-stage distillation tower to increase the adsorption and removal of specific metal ions in electronic-grade sulfuric acid. Its porous structure can not only effectively remove organic macromolecules, bacteria, viruses, anionic impurities and other impurities in electronic-grade sulfuric acid, but also effectively remove Au, Ag, Pt, Ni, and Bi metal ion impurities, thereby meeting the high purity requirements of various industries for electronic-grade sulfuric acid and the sharp increase in the demand for high-purity sulfuric acid.

[0038] (2) The preparation method of the present invention is simple to operate and has low cost, and can effectively solve the problem of high content of specific metal ion impurities in the existing high-purity sulfuric acid purification.

[0039] (3) The novel super-adsorbent material prepared by the present invention, which is a composite membrane material containing PVDF / SGO nanoporous membrane material and PVDF / GO electrospinning membrane material, has a reasonable formula design and effectively improves the service life of the membrane material. BRIEF DESCRIPTION OF THE DRAWINGS

[0040] Figure 1 This is a scanning electron microscope (SEM) test image (50 μm) of the composite film material of the preferred embodiment 2 of the present invention;

[0041] Figure 2 for Figure 1 Scanning electron microscope (SEM) test image of the area at A in the middle (5 μm);

[0042] Figure 3 This is a scanning electron microscope (SEM) test image (500 μm) of the composite film material of the preferred embodiment 2 of the present invention;

[0043] Figure 4 Scanning electron microscope SEM and EDS test images (10 μm) of graphene oxide GO used in preferred embodiment 2 of the present invention;

[0044] Figure 5 To obtain Figure 4 The distribution of carbon and oxygen elements in the EDS test at ① and ② in the SEM image;

[0045] Figure 6 To obtain Figure 4 The carbon and oxygen content in the EDS test at ① in the SEM image;

[0046] Figure 7 To obtain Figure 4 The carbon and oxygen content in the EDS test at point ② in the SEM image;

[0047] Figure 8 Another SEM and EDS test image (10 μm) of graphene oxide GO used in the preferred embodiment 2 of the present invention;

[0048] Fig. 9 To obtain Figure 8 The distribution diagram of carbon and oxygen elements in the EDS test at ③, ④, and ⑤ in the SEM image;

[0049] Fig.10 To obtain Figure 8 The carbon and oxygen content in the EDS test at point ③ in the SEM image;

[0050] Fig.11 To obtain Figure 8 The carbon and oxygen content in the EDS test at ④ in the SEM image;

[0051] Fig.12 To obtain Figure 8 The carbon and oxygen element contents in the EDS test at ⑤ in the SEM image;

[0052] Fig.13 The SEM test image (10 μm) of the sulfonated graphene oxide SGO used in the preferred embodiment 2 of the present invention;

[0053] Fig.14 To obtain Fig.13 The distribution of carbon and oxygen elements in the EDS test at ① and ② in the SEM image;

[0054] Fig.15 To obtain Fig.13 The carbon, oxygen, sulfur and nitrogen content in the EDS test at ① in the SEM image;

[0055] Fig.16 To obtain Fig.13The carbon, oxygen, sulfur and nitrogen content in the EDS test at point ② in the SEM image;

[0056] Fig.17 Another SEM and EDS test image (10 μm) of the sulfonated graphene oxide SGO used in the preferred embodiment 2 of the present invention;

[0057] Fig.18 To obtain Fig.17 The distribution diagram of carbon, oxygen, sulfur and nitrogen elements in the EDS test at point ③ in the SEM image;

[0058] Fig.19 To obtain Fig.17 The carbon, oxygen, sulfur and nitrogen content in the EDS test at point ③ in the SEM image;

[0059] Fig. 20 This is a data diagram of the removal of Au metal ions from high-purity sulfuric acid by the composite membrane material of the preferred embodiment 2 of the present invention;

[0060] Fig.21 This is a data diagram of the removal of Ag metal ions from high-purity sulfuric acid by the composite membrane material of the preferred embodiment 2 of the present invention;

[0061] Fig. 22 This is a data diagram of the removal of Pt metal ions from high-purity sulfuric acid by the composite membrane material of the preferred embodiment 2 of the present invention;

[0062] Fig.23 This is a data diagram of the removal of Ni metal ions from high-purity sulfuric acid by the composite membrane material of the preferred embodiment 2 of the present invention;

[0063] Fig.24 This is a data diagram of the removal of Bi metal ions from high-purity sulfuric acid by the composite membrane material of the preferred embodiment 2 of the present invention;

[0064] Among them, 11. PVDF / GO electrospinning membrane; 12. PVDF / SGO nanoporous membrane. DETAILED DESCRIPTION

[0065] The present invention is further described below in conjunction with the accompanying drawings and specific implementation methods. It should be noted that, under the premise of no conflict, the various embodiments or technical features described below can be arbitrarily combined to form a new embodiment.

[0066] In the present invention, unless otherwise specified, all parts and percentages are by weight, and the equipment and raw materials used can be purchased from the market or are commonly used in the art. The methods in the following embodiments are all conventional methods in the art unless otherwise specified.

[0067] The present invention provides a composite membrane material for reducing the content of Au / Ag / Pt / Ni / Bi in electronic grade sulfuric acid, wherein the composite membrane material comprises a PVDF / SGO nanoporous membrane material and a PVDF / GO electrostatic spinning membrane material composited on the surface of the PVDF / SGO nanoporous membrane material;

[0068] The PVDF / SGO nanoporous membrane material uses N-methylpyrrolidone (NMP) as a solvent, polyvinylidene fluoride (PVDF) as a polymer, glass fiber and graphite powder as additives, and sulfonated graphene oxide (SGO) as a chemical adsorption complexing agent, and is configured into a membrane liquid with a viscosity suitable for scraping and stable, and scraping and coating to obtain a PVDF / SGO nanoporous membrane material;

[0069] The PVDF / GO electrospinning membrane material uses N,N-dimethylformamide (DMF) as a solvent, polyvinylidene fluoride (PVDF) as a polymer, and graphene oxide (GO) as a chemical adsorption complexing agent, which are configured into a stable membrane solution with a viscosity suitable for electrospinning, and the PVDF / GO electrospinning membrane material is obtained through spinning.

[0070] Wherein, the preparation method of sulfonated graphene oxide SGO of the present invention is as follows:

[0071] 11) adding graphene oxide to ultrapure water, and ultrasonically dispersing for 50 to 70 minutes to obtain a suspension; the amount ratio of the graphene oxide to the ultrapure water is 0.1 to 1 g: 250 ml;

[0072] 12) adding p-aminobenzenesulfonic acid to the suspension obtained in step 1), stirring under an oil bath condition of 75-85° C., reacting for 5-7 hours, and obtaining an SGO precipitate; the mass ratio of p-aminobenzenesulfonic acid to graphene oxide is 0.2-0.8:1;

[0073] 13) centrifugally filtering the SGO precipitate obtained in step 2) at 4500-5500 rpm, and washing with ultrapure water for multiple times to remove residual p-phenylaminosulfonic acid to obtain a flocculent product;

[0074] 14) The flocculent product is centrifuged at ultra-high speed of 4500-5500 rpm, the supernatant is removed after centrifugation, and the product is freeze-dried to obtain sulfonated graphene oxide.

[0075] The graphene oxide GO used in preparing the sulfonated graphene oxide SGO or the graphene oxide GO used in preparing the scraping liquid of the present invention is prepared by the following steps:

[0076] 21) At room temperature, add graphite powder and sodium nitrate into a reactor and add a rotor; pour in 300 ml of concentrated sulfuric acid and stir with magnetic force; the amount ratio of graphite powder, sodium nitrate and concentrated sulfuric acid is 3-5 g: 2-3 g: 100 ml;

[0077] 22) Slowly add potassium permanganate into the reactor under ice bath, cover with plastic wrap, react at room temperature for 4 days, stir 2 to 3 times a day to release heat; the mass ratio of potassium permanganate to graphite powder is 3 to 5:1;

[0078] 23) After 4 days of reaction, slowly add 500-1000 ml of deionized water several times, stir, and release heat; add 50-100 ml of hydrogen peroxide, stir several times, and the reaction will form a golden sand-like graphite oxide dispersion, and cool to room temperature;

[0079] 24) The golden sand-like graphite oxide dispersion is centrifuged for the first time at 4500-5500 rpm for 5 min, the upper layer is discarded after centrifugation, deionized water is added to disperse the gel-like graphene oxide, and the mixture is stirred and centrifuged for the second time at 4500-5500 rpm, and the upper layer is discarded after centrifugation to remove sulfuric acid;

[0080] 25) Add deionized water, shake well, perform ice bath ultrasound for 3-5 min, perform a third centrifugation at 1500-2500 rpm for 3-5 min, repeat this step until the upper layer liquid is no longer viscous, collect the lower layer liquid, and freeze-dry the lower layer liquid to obtain graphene oxide GO.

[0081] The mass ratio of carbon to oxygen in the graphene oxide prepared by the present invention is 6:4; the mass ratio of carbon, oxygen, sulfur and nitrogen in the sulfonated graphene oxide prepared is 6.2:3.7:0.4:0.5.

[0082] As a further preferred embodiment, in the PVDF / SGO nanoporous membrane material, the mass ratio of N-methylpyrrolidone to polyvinylidene fluoride is 85-95:5-15, and the sum of the mass percentages of the two components is 100%; the amount of the glass fiber is 5-20% of the total mass of N-methylpyrrolidone and polyvinylidene fluoride, the amount of the graphite powder is 5-15% of the total mass of N-methylpyrrolidone and polyvinylidene fluoride, and the amount of the graphene oxide is 0.5-2% of the total mass of N-methylpyrrolidone and polyvinylidene fluoride.

[0083] As a further preferred embodiment, in the PVDF / GO electrospinning membrane, the mass ratio of N,N-dimethylformamide to polyvinylidene fluoride is 85-95:5-15, the sum of the mass percentages of the two components is 100%, and the amount of graphene oxide used is 0.01-6% of the total mass of N,N-dimethylformamide and polyvinylidene fluoride.

[0084] As a further preferred embodiment, the molecular weight of the polyvinylidene fluoride used in the present invention is 300,000 to 500,000.

[0085] As a further preferred embodiment, the composite membrane material is at least a three-layer structure, including a PVDF / SGO nanoporous membrane material and a PVDF / GO electrospinning membrane material respectively composited on the upper surface and the lower surface of the PVDF / SGO nanoporous membrane material.

[0086] The present invention also provides a method for preparing a composite film material for reducing the content of Au / Ag / Pt / Ni / Bi in electronic grade sulfuric acid, comprising the following steps:

[0087] (1) Weighing 85-95% by weight of N-methylpyrrolidone and 5-15% by weight of polyvinylidene fluoride, the sum of the mass percentages of the two components being 100%, and mixing the above components to prepare a basic scraping film solution; weighing 0.01-6% by weight of graphene oxide based on the total weight of the basic film solution, and then mixing it with the basic film solution to prepare an electrospinning film solution for standby use;

[0088] (2) Weighing 85-95% by weight of N,N-dimethylformamide and 5-15% by weight of polyvinylidene fluoride, the sum of the mass percentages of the two components being 100%, and mixing the above components to prepare a basic scraping liquid; weighing 5-20% by weight of glass fiber, 5-15% by weight of graphite powder, and 0.5-2% by weight of sulfonated graphene oxide based on the total weight of the basic scraping liquid, and mixing them with the basic scraping liquid to prepare a scraping liquid;

[0089] (3) pouring the scraping liquid obtained in step (2) into a scraping coater, scraping the film on a quartz plate using the scraping coater, and then soaking the film in ultrapure water for 1 to 24 hours, and drying it for 1 to 3 hours after demolding to obtain a PVDF / SGO nanoporous membrane material;

[0090] (4) Using an electrospinning machine, the electrospinning membrane solution prepared in step (1) is spun on the upper and lower surfaces of the PVDF / SGO nanoporous membrane material in step (3) to form upper and lower layers of PVDF / GO electrospinning membrane material, and after drying for 0.5 to 2 hours, a composite membrane material is obtained.

[0091] As a further preferred embodiment, the specific method for preparing the electrospinning membrane solution in step (1) is as follows:

[0092] (11) preparing a base membrane solution: weighing N,N-dimethylformamide and polyvinylidene fluoride, mixing the above components, stirring for 1 to 3 hours in a stirrer, and vacuum defoaming for 5 to 30 minutes to obtain a base membrane solution;

[0093] (12) Preparing an electrospinning membrane solution: Weighing graphene oxide, mixing the graphene oxide with the base membrane solution obtained in step (11), stirring with a stirrer for 1 to 3 hours, and vacuum defoaming for 5 to 30 minutes to obtain an electrospinning membrane solution.

[0094] As a further preferred embodiment, the specific method for preparing the scraping liquid in step (2) is as follows:

[0095] (21) preparing a basic scraping solution: weighing N-methylpyrrolidone and polyvinylidene fluoride, mixing the above components, stirring for 1 to 3 hours in a stirrer, and vacuum defoaming for 5 to 30 minutes to obtain a basic scraping solution;

[0096] (22) preparing a scraping liquid: weighing glass fiber, graphite powder, and sulfonated graphene oxide, mixing the glass fiber, graphite powder, sulfonated graphene oxide, and the basic scraping liquid obtained in step (21), stirring in a mixer for 1 to 3 hours, and vacuum defoaming for 5 to 30 minutes to obtain a scraping liquid.

[0097] As a further preferred embodiment, in step (3), the process parameters of the scraping coater are as follows: the reciprocating scraping speed is 8 to 12 mm / s, the scraping temperature is at room temperature, and the film thickness of the film scraped by the scraping coater on the quartz plate is 200 to 1000 μm.

[0098] As a further preferred embodiment, in step (4), the spinning conditions are: spinning voltage is 8 to 16 kV, injection speed is 0.6 to 1.4 mL / h, and spinning time is 2 to 8 h.

[0099] The following are specific embodiments of the present invention. Unless otherwise specified, the raw materials, equipment, etc. used in the following embodiments can be obtained by purchase.

[0100] Example 1

[0101] A composite membrane material for reducing the metal ion content in electronic grade sulfuric acid is prepared by the following steps:

[0102] (1) Weigh 85% by weight of N-methylpyrrolidone NMP and 15% by weight of polyvinylidene fluoride PVDF, the sum of the mass percentages of the two components being 100%, mix the above components, stir for 1 hour with a blender, and defoam for 5 minutes in a vacuum to obtain a base membrane solution; weigh 0.05% by weight of graphene oxide GO based on the total weight of the base membrane solution, and then mix the graphene oxide GO with the base membrane solution, stir for 1 hour with a blender, and defoam for 5 minutes in a vacuum to prepare an electrospinning membrane solution for standby use; wherein the PVDF is selected from Solef 6010 PVDF of Solvay, USA, and has a molecular weight of 400,000.

[0103] (2) Weigh 85% by weight of N,N-dimethylformamide DMF and 15% by weight of polyvinylidene fluoride PVDF, the sum of the mass percentages of the two components being 100%, mix the above components, stir in a blender for 1 hour, and defoam in a vacuum oven for 5 minutes to prepare a basic scraping solution; weigh 5% by weight of glass fiber, 5% by weight of graphite powder, and 0.5% by weight of sulfonated graphene oxide SGO based on the total weight of the basic scraping solution, mix them with the basic scraping solution, stir in a blender for 1 hour, and defoam in a vacuum oven for 5 minutes to prepare a scraping solution; wherein, PVDF is selected from PVDF model Solef6010 of Solvay, USA, and has a molecular weight of 400,000.

[0104] (3) pouring the scraping liquid obtained in step (2) into a scraping coater, the process parameters of the scraping coater are as follows: the reciprocating scraping speed is 8 mm / s, the scraping temperature is at room temperature, and the scraping coater is used to scrape a film with a thickness of 200 μm on a quartz plate, and then the film is placed in ultrapure water and soaked for 1 hour, and then dried for 1 hour after demolding to obtain a PVDF / SGO nanoporous membrane material;

[0105] (4) Using an electrospinning machine, the electrospinning membrane liquid prepared in step (1) is spun on the upper and lower surfaces of the PVDF / SGO nanoporous membrane material in step (3) to form upper and lower layers of PVDF / GO electrospinning membrane material, wherein the spinning conditions are as follows: spinning voltage of 8 kV, injection speed of 0.6 mL / h, spinning time of 2 h, and drying for 0.5 h to obtain a composite membrane material.

[0106] Example 2

[0107] A composite membrane material for reducing the metal ion content in electronic grade sulfuric acid is prepared by the following steps:

[0108] (1) Weigh 90% by weight of N-methylpyrrolidone and 10% by weight of polyvinylidene fluoride, the sum of the mass percentages of the two components being 100%, mix the above components, stir for 2 hours with a stirrer, and then defoam for 15 minutes in a vacuum to obtain a base membrane liquid; weigh 3% by weight of graphene oxide based on the total weight of the base membrane liquid, and then mix the graphene oxide with the base membrane liquid, stir for 2 hours with a stirrer, and then defoam for 15 minutes in a vacuum to prepare an electrospinning membrane liquid for standby use; wherein PVDF is selected from Solef 6010 PVDF of Solvay, USA, and has a molecular weight of 400,000.

[0109] (2) Weigh 90% by weight of N,N-dimethylformamide and 10% by weight of polyvinylidene fluoride, the sum of the mass percentages of the two components being 100%, mix the above components, stir for 2 hours with a mixer, and then defoam for 15 minutes in a vacuum to prepare a basic scraping liquid; weigh 15% of the total weight of the basic scraping liquid, glass fiber, 10% of graphite powder, and 1% of sulfonated graphene oxide, mix the components with the basic scraping liquid, stir for 2 hours with a mixer, and then defoam for 15 minutes in a vacuum to prepare a scraping liquid; wherein, PVDF is selected from PVDF model Solef6010 of Solvay, USA, and has a molecular weight of 400,000.

[0110] (3) pouring the scraping liquid obtained in step (2) into a scraping coater, the process parameters of the scraping coater are as follows: the reciprocating scraping speed is 10 mm / s, the scraping temperature is at room temperature, and the scraping coater is used to scrape a film with a thickness of 300 μm on a quartz plate, and then the film is placed in ultrapure water and soaked for 12 hours, and then dried for 2 hours after demolding to obtain a PVDF / SGO nanoporous membrane material;

[0111] (4) Using an electrospinning machine, the electrospinning membrane liquid prepared in step (1) is spun on the upper and lower surfaces of the PVDF / SGO nanoporous membrane material in step (3) to form upper and lower layers of PVDF / GO electrospinning membrane material, wherein the spinning conditions are as follows: spinning voltage of 14 kV, injection speed of 1 mL / h, spinning time of 4 h, and drying for 1.5 h to obtain a composite membrane material.

[0112] Example 3

[0113] A composite membrane material for reducing the metal ion content in electronic grade sulfuric acid is prepared by the following steps:

[0114] (1) Weigh 95% by weight of N-methylpyrrolidone and 5% by weight of polyvinylidene fluoride, the sum of the two components being 100% by weight, mix the above components, stir for 3 hours with a stirrer, and defoam for 30 minutes in a vacuum to obtain a base membrane liquid; weigh 6% by weight of graphene oxide based on the total weight of the base membrane liquid, and then mix the graphene oxide with the base membrane liquid, stir for 3 hours with a stirrer, and defoam for 30 minutes in a vacuum to prepare an electrospinning membrane liquid for standby use; wherein PVDF is selected from Solef 6010 PVDF of Solvay, USA, and has a molecular weight of 400,000.

[0115] (2) Weigh 95% by weight of N,N-dimethylformamide and 5% by weight of polyvinylidene fluoride, the sum of the mass percentages of the two components being 100%, mix the above components, stir for 3 hours with a mixer, and then defoam for 30 minutes in a vacuum to prepare a basic scraping liquid; weigh 20% by weight of glass fiber, 15% by weight of graphite powder, and 2% by weight of sulfonated graphene oxide based on the total weight of the basic scraping liquid, mix the components with the basic scraping liquid, stir for 3 hours with a mixer, and then defoam for 30 minutes in a vacuum to prepare a scraping liquid; wherein, PVDF is selected from PVDF model Solef6010 of Solvay, USA, and has a molecular weight of 400,000.

[0116] (3) pouring the film-scraping liquid obtained in step (2) into a film-scraping coater, the process parameters of the film-scraping coater are as follows: the reciprocating film-scraping speed is 12 mm / s, the film-scraping temperature is at room temperature, and the film-scraping coater is used to scrape a film with a thickness of 1000 μm on a quartz plate, and then the film is immersed in ultrapure water for 24 hours, and then dried for 3 hours after demolding to obtain a PVDF / SGO nanoporous membrane material;

[0117] (4) Using an electrospinning machine, the electrospinning membrane liquid prepared in step (1) is spun on the upper and lower surfaces of the PVDF / SGO nanoporous membrane material in step (3) to form upper and lower layers of PVDF / GO electrospinning membrane material, wherein the spinning conditions are as follows: spinning voltage of 16 kV, injection speed of 1.4 mL / h, spinning time of 8 h, and drying for 2 h to obtain a composite membrane material.

[0118] The sulfonated graphene oxide SGO of Examples 1-3 is prepared by the following steps:

[0119] 11) adding graphene oxide GO to ultrapure water and ultrasonically dispersing for 60 minutes to obtain a suspension; the amount ratio of graphene oxide to ultrapure water is 0.5g:250ml;

[0120] 12) Add 0.2 g aminobenzenesulfonic acid to the suspension obtained in step 11), stir in an oil bath at 80° C., and react for 6 h to obtain an SGO precipitate;

[0121] 13) centrifugally filtering the SGO precipitate obtained in step 12) at 5000 rpm, and washing with ultrapure water for multiple times to remove residual p-phenylaminosulfonic acid to obtain a flocculent product;

[0122] 14) The flocculent product is centrifuged at an ultra-high speed of 5000 rpm, the supernatant is removed after centrifugation, and the product is freeze-dried to obtain sulfonated graphene oxide.

[0123] Wherein, the graphene oxide GO of Examples 1-3 or the graphene oxide GO in step 11) is prepared by the following steps:

[0124] 21) At room temperature, add 10g of graphite powder and 7.5g of sodium nitrate into a reactor and add a rotor; pour in 300ml of concentrated sulfuric acid and stir magnetically;

[0125] 22) Slowly add 40 g of potassium permanganate into the reactor under an ice bath, cover with plastic wrap, and react at room temperature for 4 days, stirring 2-3 times a day to release heat;

[0126] 23) After 4 days of reaction, slowly add 800 ml of deionized water several times, stir and release heat; add 60 ml of hydrogen peroxide, stir several times, the reaction turns into a golden sand-like graphite oxide dispersion, and cool to room temperature;

[0127] 24) The golden sand-like graphite oxide dispersion is centrifuged for the first time at 5000 rpm for 5 min, the upper layer is discarded after centrifugation, deionized water is added to disperse the gel-like graphene oxide, and the mixture is stirred and centrifuged for the second time at 5000 rpm. The upper layer is discarded after centrifugation to remove sulfuric acid;

[0128] 25) Add deionized water, shake well, perform ice bath ultrasound for 5 min, perform a third centrifugation at 2000 rpm for 5 min, repeat this step until the upper layer liquid is no longer viscous, collect the lower layer liquid, and freeze-dry the lower layer liquid to obtain graphene oxide GO.

[0129] Comparative Example 1

[0130] Compared with Example 2, the difference of Comparative Example 1 is that the membrane material is only a single-layer membrane material of PVDF / GO electrospinning membrane, lacks PVDF / SGO nanoporous membrane material, and the other conditions are the same as those of Example 2.

[0131] Comparative Example 2

[0132] Compared with Example 2, the difference of Comparative Example 2 is that the membrane material is only a single-layer membrane material of PVDF / SGO nanoporous membrane, lacks PVDF / GO electrospinning membrane material, and the other conditions are the same as those of Example 2.

[0133] Comparative Example 3

[0134] Compared with Example 2, the difference of Comparative Example 3 is that the polyvinylidene fluoride PVDF in steps (1) and (2) is selected from PVDF of model number Solef 1015 produced by Solvay, USA, with a molecular weight of 1 million, and the other conditions are the same as those in Example 2.

[0135] Comparative Example 4

[0136] Compared with Example 2, the difference of Comparative Example 4 is that the graphene oxide GO used in step (1) is purchased from graphene oxide model S926168 of MacLean Company, and the other conditions are the same as those of Example 2.

[0137] Comparative Example 5

[0138] Compared with Example 2, the difference of Comparative Example 5 is that the sulfonated graphene oxide SGO used in step (2) is purchased from the sulfonated graphene oxide model 045697616 of the exploration platform, and the other conditions are the same as those of Example 2.

[0139] Comparative Example 6

[0140] Compared with Example 2, the difference of Comparative Example 6 is that no glass fiber is added in step (2), and the other conditions are the same as those of Example 2.

[0141] Comparative Example 7

[0142] Compared with Example 2, the difference of Comparative Example 7 is that no graphite powder is added in step (2), and the other conditions are the same as those of Example 2.

[0143] Effect evaluation and performance testing

[0144] The performance of the composite membranes of Examples 1-3 and each comparative example in terms of their ability to remove specific metal ions and service life were tested. See Table 1 for the test items and results.

[0145] 1. Cross-flow filtration experiment

[0146] The composite membranes prepared in Examples 1-3 and various comparative examples were tested using a cross-flow filtration integrated device. The membrane is assembled into a cross-flow filtration integrated device, and then the same batch of electronic-grade sulfuric acid is introduced into the liquid inlet. During cross-flow filtration, the flow of electronic-grade sulfuric acid generates two forces on the membrane surface. One is the normal force perpendicular to the membrane surface, which allows the electronic-grade sulfuric acid to pass through the membrane surface, and the other is the tangential force parallel to the membrane surface, which washes away the retained substances (including metal ions) on the membrane surface. Each time the electronic-grade sulfuric acid is filtered for 3 minutes, 1 ml of electronic-grade sulfuric acid is intercepted at the tail end of the liquid outlet; the experiment is repeated 7 times to obtain 7 electronic-grade sulfuric acid filtrates.

[0147] 2. ICP-MS experiment

[0148] The ICP-MS equipment in the Class 100 clean room was used to test the trace amount of metal ions in the sulfuric acid stock solution and the electronic grade sulfuric acid filtrate, that is, the metal ion trace amount of the samples numbered (1) high purity sulfuric acid stock solution, (2) 1st sulfuric acid filtrate, (3) 2nd sulfuric acid filtrate, (4) 3rd sulfuric acid filtrate, (5) 4th sulfuric acid filtrate, (6) 5th sulfuric acid filtrate, (7) 6th sulfuric acid filtrate, and (8) 7th sulfuric acid filtrate was tested. ① ICP-MS is the full name of Inductively Coupled Plasma-Mass Spectrometry. ICP acts as an ion source. ICP uses a high-frequency radio frequency signal applied to an inductor coil to form a high-temperature plasma inside the coil, and through the promotion of gas, the balance and continuous ionization of the plasma are guaranteed. The sample to be analyzed is sent into the atomizer by a peristaltic pump to form an aerosol, which is carried into the center of the plasma torch by the carrier gas to evaporate, decompose, excite and ionize. High-temperature plasma ionizes most elements in the sample to produce an electron and form monovalent positive ions. ② The ions in the plasma are effectively transmitted to the mass spectrometer through the ICP-MS interface; ③ The mass spectrometer is a mass screening and analyzer that detects the intensity of a certain ion by selecting ions with different mass-to-nuclear ratios (m / z) to pass through, and then analyzes and calculates the trace amount of a certain element. The test results select the trace changes of specific metal ions to explain the filtering effect of this membrane material on specific metal ions.

[0149] Table 1 shows the removal and filtration test results of specific metal ions of the composite membrane materials of each embodiment

[0150]

[0151] Table 2 Figure 4 , 8 The carbon-oxygen mass ratio test results of graphene oxide GO at five locations in the SEM image shown

[0152] Wt% ① ② ③ ④ ⑤ Carbon Atom 59.5 57.5 62.6 60.3 62.1 Oxygen Atom 40.5 42.5 37.4 39.7 37.9

[0153] Table 3 Fig.13 , 17 The carbon-oxygen mass ratio test results of sulfonated graphene oxide SGO in three locations in the SEM image shown

[0154] Wt% ① ② ③ Carbon Atom 61.0 62.7 61.2 Oxygen Atom 37.9 36.3 38.1 Sulfur Atom 0.3 0.4 0.4 Nitrogen Atom 0.8 0.5 0.3

[0155] Figure 1-3 This is a SEM test image of the PVDF / SGO composite membrane material of the preferred embodiment 2 of the present invention, as shown Figure 1-3As shown, the composite membrane prepared by the present invention can be clearly seen to have a three-layer structure, wherein the middle layer is a nanoporous layer (thickness of about 200 μm), and the two sides are electrospinning layers (each layer is about 100 μm thick), and from the cross-sectional and surface SEM images, it can be seen that the electrospinning layer and the nanoporous layer are well combined. The composite membrane can be used as a composite membrane for filtering electronic grade sulfuric acid.

[0156] Figure 4-12 The SEM and EDS test images of the graphene oxide GO prepared by the present invention are shown in the figure. As shown in the figure, the sulfonated graphene oxide GO prepared by the present invention is in the form of flakes, the thickness of a single layer of graphene oxide is about 0.8-1.2nm, and the average radial size is 40-60μm. The mass ratio of C to O in the sulfonated graphene oxide SGO prepared by this patent is approximately 6:4.

[0157] Figure 13-19 The SEM and EDS test images of the sulfonated graphene oxide SGO prepared by the present invention are shown in the figure. As shown in the figure, the sulfonated graphene oxide SGO prepared by the present invention is in the form of flakes, the thickness of a single layer of sulfonated graphene oxide is about 0.8-1.2nm, and the average radial size is 40-60μm. The mass ratio of C, O, S, and N in the sulfonated graphene oxide SGO prepared by this patent is approximately 6.2:3.7:0.4:0.5.

[0158] As shown in the table above and Figure 20-24 As shown, by preparing a new type of super adsorption material-composite membrane material, the content of specific metal ions such as Au, Ag, Pt, Ni, and Bi in electronic-grade sulfuric acid can be effectively reduced, and the problem of high impurity content of specific metal ions in the existing high-purity sulfuric acid purification can be effectively solved.

[0159] In addition, in Comparative Example 1, the membrane material is only a single-layer membrane material of PVDF / GO electrospinning membrane, which cannot specifically filter Ag and Pt ions.

[0160] In Comparative Example 2, the membrane material is only a single-layer membrane material of PVDF / SGO nanoporous membrane, which cannot specifically filter Ni and Bi ions.

[0161] In Comparative Example 3, the PVDF with a molecular weight of 1 million has a poor film-forming effect and an unsatisfactory filtering effect.

[0162] Comparative Examples 4-5 use externally purchased SGO / GO. Since the externally purchased SGO / GO has more impurities, more metal ion impurities are introduced during the filtration process, so the percentage exceeds 100%.

[0163] In Comparative Examples 6-7, since glass fiber and graphite powder additives were not added during the membrane preparation process, the membrane could not be formed, could not filter trace amounts of metal ions, and could not test the filtration capacity of the membrane.

[0164] 3. Film material service life test

[0165] In the cross-flow filtration experiment, the membrane materials of each example were continuously used to filter and purify sulfuric acid. After 50 filtrations, the membrane materials were taken out and the damage of the membrane materials was observed. The results showed that the nanoporous membrane material prepared by the present invention was not damaged after 50 filtrations under a microscope.

[0166] The novel super-adsorption material prepared by the present invention, namely the composite membrane material, not only effectively solves the problem of high content of specific metal ion impurities in the existing high-purity sulfuric acid purification, but also has a reasonable formula design and effectively improves the service life of the membrane material.

[0167] The above-mentioned embodiments are only preferred embodiments of the present invention and cannot be used to limit the scope of protection of the present invention. Any non-substantial changes and substitutions made by technicians in this field on the basis of the present invention shall fall within the scope of protection required by the present invention.

Claims

1. A composite film material for reducing the content of Au / Ag / Pt / Ni / Bi in electronic grade sulfuric acid, characterized in that: The composite membrane material includes a PVDF / SGO nanoporous membrane material and a PVDF / GO electrostatic spinning membrane material composited on the surface of the PVDF / SGO nanoporous membrane material; The PVDF / SGO nanoporous membrane material uses N-methylpyrrolidone as a solvent, polyvinylidene fluoride as a polymer, glass fiber and graphite powder as additives, and sulfonated graphene oxide as a chemical adsorption complexing agent, and is configured into a membrane liquid with a viscosity suitable for scraping and stable, and is coated by scraping to obtain a PVDF / SGO nanoporous membrane material; The PVDF / GO electrostatic spinning membrane material uses N,N-dimethylformamide as a solvent, polyvinylidene fluoride as a polymer, and graphene oxide as a chemical adsorption complexing agent, which are configured into a stable membrane solution with a viscosity suitable for electrostatic spinning, and the PVDF / GO electrostatic spinning membrane material is obtained through spinning.

2. The composite film material for reducing the content of Au / Ag / Pt / Ni / Bi in electronic grade sulfuric acid according to claim 1, characterized in that: In the PVDF / SGO nanoporous membrane material, the mass ratio of N-methylpyrrolidone to polyvinylidene fluoride is 85-95:5-15, and the sum of the mass percentages of the two components is 100%; the amount of the glass fiber is 5-20% of the total mass of N-methylpyrrolidone and polyvinylidene fluoride, the amount of the graphite powder is 5-15% of the total mass of N-methylpyrrolidone and polyvinylidene fluoride, and the amount of the graphene oxide is 0.5-2% of the total mass of N-methylpyrrolidone and polyvinylidene fluoride.

3. The composite film material for reducing the content of Au / Ag / Pt / Ni / Bi in electronic grade sulfuric acid according to claim 1, characterized in that: In the PVDF / GO electrospinning membrane, the mass ratio of N,N-dimethylformamide to polyvinylidene fluoride is 85-95:5-15, the sum of the mass percentages of the two components is 100%, and the amount of graphene oxide used is 0.01-6% of the total mass of N,N-dimethylformamide and polyvinylidene fluoride.

4. The composite film material for reducing the content of Au / Ag / Pt / Ni / Bi in electronic grade sulfuric acid according to claim 1, characterized in that: The molecular weight of the polyvinylidene fluoride is 300,000 to 500,000.

5. The composite film material for reducing the content of Au / Ag / Pt / Ni / Bi in electronic grade sulfuric acid according to claim 1, characterized in that: The composite membrane material is at least a three-layer structure, including a PVDF / SGO nanoporous membrane material and a PVDF / GO electrostatic spinning membrane material respectively composited on the upper surface and the lower surface of the PVDF / SGO nanoporous membrane material.

6. A method for preparing a composite film material for reducing the content of Au / Ag / Pt / Ni / Bi in electronic grade sulfuric acid, characterized in that: The following steps are involved: (1) Weighing 85-95% by weight of N-methylpyrrolidone and 5-15% by weight of polyvinylidene fluoride, the sum of the mass percentages of the two components being 100%, and mixing the above components to prepare a basic scraping film solution; weighing 0.01-6% by weight of graphene oxide based on the total weight of the basic film solution, and then mixing it with the basic film solution to prepare an electrospinning film solution for standby use; (2) Weighing 85-95% by weight of N,N-dimethylformamide and 5-15% by weight of polyvinylidene fluoride, the sum of the mass percentages of the two components being 100%, and mixing the above components to prepare a basic scraping liquid; weighing 5-20% by weight of glass fiber, 5-15% by weight of graphite powder, and 0.5-2% by weight of sulfonated graphene oxide based on the total weight of the basic scraping liquid, and mixing them with the basic scraping liquid to prepare a scraping liquid; (3) pouring the scraping liquid obtained in step (2) into a scraping coater, scraping the film on a quartz plate using the scraping coater, and then soaking the film in ultrapure water for 1 to 24 hours, and drying it for 1 to 3 hours after demolding to obtain a PVDF / SGO nanoporous membrane material; (4) Using an electrospinning machine, the electrospinning membrane solution prepared in step (1) is spun on the upper and lower surfaces of the PVDF / SGO nanoporous membrane material in step (3) to form upper and lower layers of PVDF / GO electrospinning membrane material, and after drying for 0.5 to 2 hours, a composite membrane material is obtained.

7. The method for preparing a composite film material for reducing the content of Au / Ag / Pt / Ni / Bi in electronic grade sulfuric acid according to claim 6, characterized in that: The specific preparation method of the electrospinning membrane solution in step (1) is as follows: (11) preparing a base membrane solution: weighing N,N-dimethylformamide and polyvinylidene fluoride, mixing the above components, stirring for 1 to 3 hours in a stirrer, and vacuum defoaming for 5 to 30 minutes to obtain a base membrane solution; (12) Preparing an electrospinning membrane solution: Weighing graphene oxide, mixing the graphene oxide with the base membrane solution obtained in step (11), stirring with a stirrer for 1 to 3 hours, and vacuum defoaming for 5 to 30 minutes to obtain an electrospinning membrane solution.

8. The method for preparing a composite film material for reducing the content of Au / Ag / Pt / Ni / Bi in electronic grade sulfuric acid according to claim 6, characterized in that: The specific preparation method of the scraping liquid in step (2) is as follows: (21) preparing a basic scraping solution: weighing N-methylpyrrolidone and polyvinylidene fluoride, mixing the above components, stirring for 1 to 3 hours in a stirrer, and vacuum defoaming for 5 to 30 minutes to obtain a basic scraping solution; (22) preparing a scraping liquid: weighing glass fiber, graphite powder, and sulfonated graphene oxide, mixing the glass fiber, graphite powder, sulfonated graphene oxide, and the basic scraping liquid obtained in step (21), stirring in a mixer for 1 to 3 hours, and vacuum defoaming for 5 to 30 minutes to obtain a scraping liquid.

9. The method for preparing a composite film material for reducing the content of Au / Ag / Pt / Ni / Bi in electronic grade sulfuric acid according to claim 6, characterized in that: In step (3), the process parameters of the scraping coater are as follows: the reciprocating scraping speed is 8-12 mm / s, the scraping temperature is at room temperature, and the film thickness of the film scraped by the scraping coater on the quartz plate is 200-1000 μm.

10. The method for preparing a composite film material for reducing the content of Au / Ag / Pt / Ni / Bi in electronic grade sulfuric acid according to claim 6, characterized in that: In step (4), the spinning conditions are: spinning voltage is 8 to 16 kV, injection speed is 0.6 to 1.4 mL / h, and spinning time is 2 to 8 h.

Citation Information

Patent Citations

  • Graphene / black phosphorus nanosheet / sulfur-containing ionic liquid composite aerogel and preparation method thereof

    CN107416846A

  • Modified polyimide nanofiber membrane as well as preparation and application thereof

    CN109763259A

  • Micro-nano fiber filter disc with adsorption and catalytic harm reduction mechanisms, and preparation method and application thereof

    CN110860134A

  • Method for efficiently preparing ultra-clean high-purity sulfuric acid

    CN115010098A

  • Hydrophobic PVDF-GO nanofiber membrane, preparation method and application

    CN115110203A